THE IMPACT OF ZINC STATUS ON THE COURSE AND SEVERITY OF COVID-19: A SYSTEMATIC REVIEW - Boyarchuk, Oksana R.; Volianska, Liubov A.; Perestiuk, Vita O.; Kosovska, Tetyana M. (Eastern Ukrainian Medical Journal, 2026)
Introduction. Zinc deficiency can negatively impact immune responses by altering immune cell quantity and function, increasing pro-inflammatory mediators, and elevating reactive oxygen species, all of which contribute to disease development and progression. The aim of this study was to determine the prevalence of hypozincemia in COVID-19 patients and assess the impact of zinc levels on the course of theSARS-CoV-2infection based on a systematic review of available literature sources. Materials and Methods. A search for relevant studies was conducted in the PubMed, Scopus, ResearchGate, and Wiley Online Library databases from 2020 to February 5, 2025. The following key terms were used in various combinations: Zn, COVID-19; Zn, SARS-CoV-2; Zinc, COVID-19; Zinc, SARS-CoV-2. Results. A total of 2,048 articles were identified through database searches. Twenty-five publications met the inclusion criteria and were analyzed, of which only four focused on pediatric populations. The median cohort age was 55.8 years (IQR: 34.1–72.3). The median prevalence of zinc deficiency in serum among study groups was 32.8%, ranging from 0% to 96%. All studies that compared COVID-19 patients to controls reported lower zinc levels in the infected group. In 69.2% of cases, hypozincemia was significantly more frequent in severe COVID-19 cases (9/13 studies). A relationship between zinc levels and complications affecting various organ systems was established in 100% of cases (3/3 studies). The impact of zinc status on hospitalization duration was observed in 72.7% of studies (8/11 studies). No significant association was found between zinc levels and ICU admission in any study. In 54.6% of cases, zinc status influenced mortality due to acute SARS-CoV-2 infection (6/11 studies). Conclusions. This systematic review revealed a wide variability in the prevalence of hypozincemia among COVID-19 patients. Zinc status had the greatest impact on the development of complications, hospitalization duration, disease severity, and mortality, particularly in adults.